2018
DOI: 10.1186/s12967-018-1728-8
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and prognostic significance of BCAR3 expression in patients with multiple myeloma

Abstract: BackgroundMultiple myeloma (MM) is the plasma cell tumor, which is characterized by clonal proliferation of tumor cells, with high risk of progression to renal impairment, bone damage and amyloidosis. Although the survival rate of patients with MM has improved in the past decade, most people inevitably relapse. The treatment and prognosis of MM are still urgent problems. Breast Cancer Antiestrogen Resistance 3 (BCAR3) is a protein-coding gene that is associated with many tumors. However, there have been few st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…Our finding that BCAR3 is subject to complex post-translational regulation may be helpful in reconciling the observation that BCAR3 over-expression in cell culture increases transformed phenotypes whereas BCAR3 RNA expression correlates with favorable outcomes in patients (Guo et al, 2014, Wallez et al, 2012, Zhang et al, 2018). In addition to the phosphorylation-dependent mechanism investigated here, a previous study showed that TGFβ stimulates proteasomal degradation of BCAR3 (Guo et al, 2014), and over-expressed BCAR3 and Cas appear to stabilize each other in breast cancer cells, dependent on their mutual binding (Wallez et al, 2014).…”
Section: Discussionmentioning
confidence: 65%
“…Our finding that BCAR3 is subject to complex post-translational regulation may be helpful in reconciling the observation that BCAR3 over-expression in cell culture increases transformed phenotypes whereas BCAR3 RNA expression correlates with favorable outcomes in patients (Guo et al, 2014, Wallez et al, 2012, Zhang et al, 2018). In addition to the phosphorylation-dependent mechanism investigated here, a previous study showed that TGFβ stimulates proteasomal degradation of BCAR3 (Guo et al, 2014), and over-expressed BCAR3 and Cas appear to stabilize each other in breast cancer cells, dependent on their mutual binding (Wallez et al, 2014).…”
Section: Discussionmentioning
confidence: 65%
“…In an early study, the stem cell marker nestin strongly associated with the presence of 1q21 gain may play an important role in MM relapse [29]. Besides, a study in Beijing analysis a gene expression microarrays of 1878 MM patients and found that with the increase of the amplification level of 1q21, the expression level of BCAR3 which is a protein-coding gene associated with many tumors showed an overall downward trend, interestingly, the expression of BCAR3 gene was different statistically in the non-relapse group and the relapse group, and the expression in the non-relapse group was notably higher than that in the relapse group (P = 0.0023) [14]. In a word, a common view have get that the main cause of myeloma recurrence is persistent residual tumor cells, which are associated with clonal evolution and immune dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…And a study of 500 patients showed that NDMM with Amp1q21 had inferior 5-year event-free/overall survival compared with those non-Amp1q21 (38%/52% vs. 62%/78%, both P < .001), and relapsed patients who had Amp1q21 had inferior 5-year post-relapse survival compared with those lacking Amp1q21 at relapse (15% vs. 53%, P = .027) [13]. Besides, Amp1q21 as the secondary genetic events may contributes much to the relapse of myeloma, while the relapse rate may decrease if treating as early as possible [14], suggesting that an early treatment target on Amp1q21 in newly diagnosed MM (NDMM) may significantly decrease the relapse of MM patients.…”
Section: Ivyspring International Publishermentioning
confidence: 97%
See 1 more Smart Citation
“…Genes from the two classifiers (Table S1) [21]. In addition, it has been shown that BCAR3 can be used as a potential biomarker, and is an independent prognostic factor for Multiple myeloma [22]. Genes involved in the extracellular matrix, such as MFAP4, were also identified in the classifiers.…”
Section: Generation Of the Two Pcr Prediction Classifiersmentioning
confidence: 99%